An experimental investigation on heat transfer performance of rotating anti-/deicing component. (August 2020) - Chen, Long; Zhang, Yishu; Liu, Zhanqiang; Zhang, Yidu
Highlights: A novel rotary spray icing experiment setup considering the influence of outflow is designed. The icing and deicing characteristics of anti-/deicing component under real conditions are investigated. The rotary spray icing experiment setup can be used to study the anti-/deicing heat transfer process. The experimental results show that the maximum error between simulation data and experimental data is 1.46%. Abstract: Ice formation and accumulation on helicopter rotor seriously threaten the flight safety. In this paper, a rotary spray icing experimental study was conducted to investigate the heat transfer characteristics of electro-thermal anti-/deicing component for helicopter rotor. A scaled anti-/deicing component sample was manufactured and exposed under typical rime icing conditions for a comparative study. During the experiments, ice knife method was used to measure the uniformity of supercooled water droplets, and the dynamic ice accretion process on the sample was recorded. It was found that under the typical rime conditions, the relationship between the icing thickness of rotor surface and the distance from the icing area to the rotating center was linear. The temperature of rotor surface far away from the rotating center was the lowest, due to the maximum convection heat transfer coefficient and the maximum heat loss caused by the maximum velocity of flow field. Through the simulation experiment, the simulation results were in good agreement with the experimental data, and the maximum error between simulation data and experimental data was 1.46%, which verifying the correctness of the experimental results and the rationality and reliability of the test equipment.